Early-Phase Recovery of Cardiorespiratory Measurements after Maximal Cardiopulmonary Exercise Testing in Patients with Chronic Obstructive Pulmonary Disease. (27th November 2016) - Bellefleur, Marie; Debeaumont, David; Boutry, Alain; Netchitailo, Marie; Cuvelier, Antoine; Muir, Jean-François; Tardif, Catherine; Coquart, Jérémy
Abstract : Background . This study investigated respiratory gas exchanges and heart rate (HR) kinetics during early-phase recovery after a maximal cardiopulmonary exercise test (CPET) in patients with chronic obstructive pulmonary disease (COPD) grouped according to airflow limitation. Methods . Thirty control individuals (control group: CG) and 81 COPD patients (45 with "mild" or "moderate" airflow limitation, C O P D I - I I, versus 36 with "severe" or "very severe" COPD, C O P D I I I - I V ) performed a maximal CPET. The first 3 min of recovery kinetics was investigated for oxygen uptake (V ˙ O2 ), minute ventilation (V ˙ E ), respiratory equivalence, and HR. The time forV ˙ O2 to reach 25% (T1/4 V ˙ O2 ) of peak value was also determined and compared. Results . TheV ˙ O2, V ˙ E, and HR recovery kinetics were significantly slower in both COPD groups than CG (p < 0.05 ). Moreover, C O P D I I I - I V group had significantly higherV ˙ O2 andV ˙ E during recovery thanC O P D I - I I group (p < 0.05 ). T1/4 V ˙ O2 significantly differed between groups (p < 0.01 ;58 ± 18 s in CG, 79 ± 26 s inC O P D I - I I group, and121 ± 34 s inC O P D I I I - I V ) and was significantly correlated with forced expiratory volume in one second in COPD patients (p < 0 . 001, r = 0.53 ) and with peak power output (p < 0.001, r = 0.59 ). Conclusion . The COPD groups showed slower kinetics in the early recovery period than CG, and the kinetics varied with severity of airflow obstruction.